Vanuatu : Socio-Economic Atlas - Vanuatu National Statistical Office (World Bank, Washington, DC, 2014)
The objective of the socio-economic atlas (SEA) for Vanuatu is to present key indicators of the socioeconomic status of Vanuatu population, at the areas council level. It allows for comparisons of various development indicators across various geographical areas. The atlas has been developed through a consultative process with various Government agencies and development organizations. The atlas provides representative socio-economic indicators at the level of area council (district), which is the smallest administrative division unit in Vanuatu. Most of the indicators presented in the atlas have been derived from the Vanuatu 2009 census data, which is rich in terms of the development indicators captured. The content of the census questionnaire defines the boundaries of what indicators can be presented. The authors have used small area estimation techniques to derive estimates of consumption-based poverty and inequality, by combining the use of the 2009 census data with the 2010 household income and expenditure survey (HIES) data. A separate technical paper describes the methodology used in doing this and is available from the Vanuatu national statistical office (VNSO) and the World Bank. The atlas includes five key groups of socio-economic indicators for population. Section A covers the indicators of household wellbeing in terms of consumption-based poverty rates and inequality indices. Section B looks at the sources of livelihoods for households in terms of livestock numbers and share of households engaged in various economic activities. Section C focuses on the households' living conditions by looking at the quality of dwelling, access to water, and access to electricity. Section D explores education outcomes and shows percent of adult population with various levels of schooling. Section E looks at some indicators related to health status, such as percent of adults who smoke and consume alcohol. Section F looks at the distribution of education and health facilities, and roads and tracks in the national road network.